Tuberculin reactivity and allergic disorders in schoolchildren, Okinawa, Japan - Miyake, Y.; Arakawa, M.; Tanaka, K.; Sasaki, S.; Ohya, Y. (Clinical and experimental allergy, 2008)
Summary Background Bacillus Calmette‐Guérin (BCG) vaccination triggers a T‐helper type 1 response. Whether BCG vaccination and positive tuberculin reactivity are preventive against allergic disorders remains controversial. Objective The current cross‐sectional study investigated the relationship of BCG vaccination and tuberculin reactivity with the prevalence of allergic disorders using data from the Ryukyus Child Health Study (RYUCHS). Methods Subjects were 5717 schoolchildren aged 8–11 years in Okinawa, Japan. The RYUCHS collected information on symptoms of allergic disorders and potential confounding factors. The outcomes were based on diagnostic criteria from the International Study of Asthma and Allergies in Childhood. Data on BCG vaccination and tuberculin tests were obtained from school records. Allowance was made for grade, sex, sibship size, smoking in the household, paternal and maternal history of asthma, atopic eczema, and allergic rhinitis, and paternal and maternal educational level. Results No measurable relationship was found between BCG vaccination in infants and the prevalence of allergic disorders. Among 5567 BCG‐vaccinated children, positive tuberculin reactivity (induration 10 mm) in the first grade was independently associated with a decreased prevalence of wheeze, asthma, and atopic eczema: the multivariate odds ratios for wheeze, asthma, and atopic eczema were 0.80 (95% confidence interval [CI], 0.67–0.94), 0.78 (95% CI, 0.64–0.95), and 0.77 (95% CI, 0.62–0.95), respectively. The inverse associations were more pronounced in children with a negative parental allergic history than in those with a positive parental allergic history. There was no significant relationship between tuberculin reactivity and allergic rhinoconjunctivitis. Conclusions The findings suggest that positive tuberculin reactivity may be inversely associated with the prevalence of wheeze, asthma, and atopic eczema, but not allergic rhinoconjunctivitis, especially among Japanese children without a parental allergic history.